Penguatan Kewenangan Advokat Dalam Penegakan Hukum Berdasarkan Undang-Undang Nomor 18 Tahun 2003 - Herman, KMS; Yudhistira, Dhieno; Maksum, Umar; Azis, Miftakul (JURNAL RETENTUM, 2023)
This study aims to analyze the role of advocates in the Indonesian criminal justice system, with a focus on the challenges faced by advocates in carrying out their profession, as well as strategies for strengthening authority that can increase the effectiveness of the role of advocates in ensuring the achievement of justice. This study uses a normative legal approach with the method of analyzing statutory regulations and literature studies to examine the regulations governing the advocate profession, especially in relation to the rights of suspects, defendants, and victims in the criminal justice process. The results of the study indicate that advocates face various obstacles, including limited access to clients and evidence, pressure or intimidation from certain parties, and gaps in the quality of legal education. To overcome these challenges, policy reforms are needed that support increased access for advocates to clients and evidence, as well as legal protection for advocates from threats or intimidation. Optimizing the role of advocates in supporting a fair justice system can be achieved through effective legal assistance to perpetrators and victims, as well as strengthening advocate competence through continuing legal education and more integrated justice strategies.